Fiber optic training program with intensive experiments using both real laboratory and simulation environments - SARIKAŞ, ALİ; AK, AYÇA; YAYLA, AYŞE; ORAL, BEKİR; AYDIN, SERKAN; KESEN, UĞUR (WILEY, 2019)
This paper highlights a fiber optic training program developed according to the occupational competencies using real and simulation platforms to train young people aged between 15 and 24. The most important objective is to overcome the shortages of fiber optic employees by providing training qualifications accredited by the Fiber Optic Association. This training program was designed on three levels, and participants were tested at the end of each level. Successful participants continued with a higher level of training. Theoretical knowledge was given to the participants at the first two levels and extensive practical applications were done. At the third level, computer networks trainings were provided to identify the much more fiber optic network modules by using simulation software tool. The training program includes installation of DVB-X (Digital Video Broadcast - satellite, cable) and the FFT-X (fiber-to-the - home, building, curb) devices that have a fiber optic cable infrastructure, and point-to-point line measurements. This training program differs from similar programs due to the inclusion of effective real laboratory, simulation platform, and field practices. It is significantly found that this training program supported by more extensive real experiments and simulations besides of theoretical education increases the technical qualifications and satisfaction ratio of the participants.
Keywords: fiber optic; fiber optic laboratory; higher education; telecommunication; training